Earth’s Temperature: The Effect of the Sun, Water Vapor, and CO2 - Lightfoot, H. Douglas; Ratzer, Gerald (Journal of Basic & Applied Sciences, 2022)
The purpose of this study is to show the Sun controls the Earth’s temperature daily and over decades and millennia. A secondary objective is to show CO2 contributes to the warming of the Earth through increased enthalpy (heat content). The methodology is to record temperature and relative humidity at many weather stations around the globe to provide a picture of the constantly changing atmosphere over twelve months. Daily measurements of the molecular fraction of CO2 are converted to weight to calculate the increasing enthalpy of the atmosphere. The Sun controls Earth’s temperature through water vapor up to the dewpoint temperature line and by direct heat radiation from the Sun above it. The enthalpy contribution by CO2 from 1750 to 2022 was up to 0.0000049 kJ/kg of dry air, equivalent to a temperature increase of 0.000181oC over 272 years. The effect of CO2 on warming the Earth has a negligible increase in Earth’s temperature.